Prime Minister Decree No. 247/2004 Concerning The Executive Statutes Of Law No. 8/1997 On Investment Guarantees And Incentives = اللائحة التنفيذية لقانون ضمانات وحوافز الاستثمار رقم 8 لسنة 1997 - Egypt; The middle east library for economic services, translator. (2025)
58, 31 pages ;